A model of factors influencing cloud computing adoption among faculty members and students of higher educational institutions of Bangladesh - Rahman, Mohammad Musudur; Suhaimi, Mohd Adam; Shah, Asadullah (Institute of Electrical and Electronics Engineers Inc., 2018)
In the 21st century, education has evolved from being confined to the four walls of a classroom to a more flexible online environment using Cloud Computing (CC) technology which has brought immense technological transformation in the field of education. This technology is rapidly growing and improving the Higher Educational Institutions’ (HEIs) performance around the world, where learners can access various computer applications from remote locations through the Internet. Previous studies on cloud computing adoption have highlighted various advantages of using this technology in HEIs, mainly in the developed countries. However, in the case of developing countries like Bangladesh, lack of research on identifying factors that might influence cloud computing adoption was observed. Hence, the authors of this paper have proposed a conceptual model that identifies the factors that influence cloud computing adoption for the faculty members and students in Bangladeshi HEIs.